Disciplinary and Generic Abilities in PBL: A Study of Life Stories from the Gender Perspective in Systems Engineering Education - Sandoval-Carvajal, Maria-Marta (2018)
While it is true that socio-economic environment plays a determining role in terms of gender and entry into technological careers such as systems engineering, tendency to generate generic and disciplinary competencies from the gender point of view, is also something relevant to analyze specific actions that allow curricular changes in curricula. Recent studies show a reduction in the entry of women into systems engineering careers since several years ago. Some of these studies suggest, among other things, aspects of socio-economic perception to explain this phenomenon. In this research we want to offer a new angle of debate focused on the results of the training process by using PBL case of study in Systems Engineering grade. We were interested in exploring the generation of competencies by gender. The Tuning Latin America project, which was originated in its European counterpart, represented an effort to locate generic and disciplinary competencies of computer science practitioners with the participation of 14 universities in the region. In this study we explore the state of internalization of disciplinary and generic skills in systems engineering students based on their life histories by considering the gender perspective. The main research method used was content analysis of approximately 150 life histories of systems engineering students. Previously, a set of disciplinary and generic skills was defined based on the classification of such skills included in the Tuning Latin America project. Interviews and focus groups sessions were also used in order to validate information. The results indicate several interesting aspects. The main competence identified by men is the disciplinary competence "Apply knowledge of computer science" and for women it was a generic competence called “the teamwork ability”. The results also show evidence that the PBL and management by competencies can help visibility of competencies something that regular Systems Engineering students would not consider, especially in the case of men, who in spite of consider first some disciplinary competences, they tend to put other generic competencies in second place. This aspect, which seems not related to gender stereotypes, could also be other attractive factor to motivate women to enter Systems Engineering education. Finally, this study not only points out the differences, but also the common elements in the teaching-learning process of engineering, such as the balance between both groups of competencies. Both male and female students using the PBL and a competencies approach, show the importance of a balance between technical and generic skills, a situation that guarantees job and social integration for future professionals.